1993
DOI: 10.1021/j100104a033
|View full text |Cite
|
Sign up to set email alerts
|

Chemisorption of nitric oxide on char. 1. Reversible nitric oxide sorption

Abstract: The process of chemisorption of nitric oxide (NO) on a carbon derived from phenol-formaldehyde resin has been studied at temperatures between 323 and 473 K and at N O partial pressures between 2.02 and 10.1 kPa. The process of chemisorption can be split into two separate pathways-one a reversible chemisorptive pathway forming nitric oxide surface complexes C ( N 0 ) and the other an irreversible chemisorptive pathway yielding N2 and carbon surface oxides C ( 0 ) and C(02). The enthalpy of formation of C ( N 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 7 publications
6
44
0
Order By: Relevance
“…The addition of O2 was essential, since it increases the adsorption of nitric oxide via the catalytic oxidation of NO to NO2, producing in an increase of the NO adsorption because of the higher adsorption potential of NO2 (Yang et al, 2000;Klose and Rincon, 2007). In the absence of oxygen the NO removal efficiency was only about 5%, similar findings have been reported in the literature (DeGroot et al, 1991;Teng and Suuberg, 1993). Prior to any test, the samples were dried under an inert N2 atmosphere.…”
Section: Nitrogen Oxide Adsorptionsupporting
confidence: 86%
“…The addition of O2 was essential, since it increases the adsorption of nitric oxide via the catalytic oxidation of NO to NO2, producing in an increase of the NO adsorption because of the higher adsorption potential of NO2 (Yang et al, 2000;Klose and Rincon, 2007). In the absence of oxygen the NO removal efficiency was only about 5%, similar findings have been reported in the literature (DeGroot et al, 1991;Teng and Suuberg, 1993). Prior to any test, the samples were dried under an inert N2 atmosphere.…”
Section: Nitrogen Oxide Adsorptionsupporting
confidence: 86%
“…The presence of oxygen in the gas mixture is essential, since it increases the adsorption of nitric oxide through the catalytic oxidation of NO to NO 2 , which results in an increase of NO adsorption due to the higher adsorption potential of NO 2 (Klose and Rincón, 2007;Yang et al, 2000). In this work, experiments in the absence of oxygen showed that NO removal efficiency was only about 5%; similar findings have been reported in the literature (DeGroot et al, 1991;Teng and Suuberg, 1993). The outlet gas was directed to a gas analyser system.…”
Section: No X Adsorption Reactor Systemsupporting
confidence: 87%
“…The kinetics of NO x removal by carbon of commercial origin has been studied by many researchers (Claudino et al, 2004;Klose and Rincón, 2007;Mochida et al, 1994;Shirahama et al, 2002;Teng and Suuberg, 1993;Zhang et al, 2008) and it has been concluded that the origin, the natural impurities in the feedstock, surface chemistry and the conditions used to prepare activated carbon are the main factors that can control its efficiency for NO x reduction (Xu et al, 2003). Although there has been much research into NO x control using activated carbons, the factors controlling the NO x adsorption process are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover a deeper knowledge of the chemistry involved in the formation and the reduction of NO X is required. Many authors have performed NO heterogeneous reduction studies on carbonaceous materials using, mainly, chars from phenol-formaldehyde resins [4][5][6][7][8][9], graphites [10] and activated carbons [11][12][13]. The use of model compounds, with controlled heteroatom content and well defined functionalities, is a useful approach that has been used by other authors [14,15] to study the release of nitrogen compounds from char combustion.…”
Section: Introductionmentioning
confidence: 99%